Chitosan Beads as an Adsorbent for the Removal of Colour from Natural Rubber Wastewater - Daud, Zawawi; Nasir, Nazlizan; Awang, Halizah; Ab Aziz, Nur Adila; Ahmad, Baharin; Ridzuan, Mohd Baharudin; Tajarudin, Husnul Azan (International Journal of Integrated Engineering, 2019)
Natural rubber processing wastewater contains high concentration of organic compound, colour, nitrogen, and other contaminants. This study evaluated a chitosan bead as an adsorbent in adsorption process for natural rubber wastewater treatment. The effects of adsorbent dosage, pH, shaking speed and contact time and adsorption isotherm on colour adsorption onto chitosan beads were evaluated using batch experiments. Meanwhile, Langmuir and Freundlich isotherm models were used to validate the experimental data. Maximum removal of 71.5%, for colour was observed for an adsorbent dosage 4.5 g, pH 7, and shaking speed 150 rpm. Equilibrium was achieved in 120 min. The equilibrium data were fitted to Langmuir isotherm model when compared with Freundlich isotherm models.